Notranja učna diferenciacija in individualizacija pri pouku književnosti v heterogenih učnih skupinah tretjega vzgojno-izobraževalnega obdobja - Kerndl, Milena (Jezik in slovstvo, 2013)
The article presents one part of research into the implementation of the principles of inner educational differentiation and individualisation in literature classes. The research was carried out in the 2011/12 school year amongst teachers in heterogeneous groups of the 3rd educational cycle. The key issue investigated was the capacity of Slovenian language teachers to recognise differences between pupils, i.e., their receptive abilities and the horizon of their expectations. In relation to this, a study was also made of the implementation of the principles of inner educational differentiation and individualisation in the treatment of literary texts, which aims to systematically develop the reception ability of the individual pupil. The described capacity should be a component of every teachers literary-didactic competence. The results of the research show that teachers do not feel sufficiently competent to discriminate successfully between pupils in terms of their abilities, and therefore desire additional training in this field.
Keywords: didaktika književnosti; osnovna šola; primary school; notranja učna diferenciacija; notranja učna individualizacija; recepcijska zmožnost; književnodidaktična kompetenca učitelja